2019
DOI: 10.5194/essd-11-1917-2019
|View full text |Cite
|
Sign up to set email alerts
|

Reference crop evapotranspiration database in Spain (1961–2014)

Abstract: Abstract. Obtaining climate grids describing distinct variables is important for developing better climate studies. These grids are also useful products for other researchers and end users. The atmospheric evaporative demand (AED) may be measured in terms of the reference evapotranspiration (ETo), a key variable for understanding water and energy terrestrial balances and an important variable in climatology, hydrology and agronomy. Despite its importance, the calculation of ETo is not commonly undertaken, main… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…Several studies showed the high occurrence of severe droughts episodes in Spain through historical [28][29][30] and instrumental records [31]. Spain has strong climatic contrasts with marked spatial and seasonal differences in precipitation [32][33][34][35] and AED [36][37][38][39]. Northern Spain is characterized by its humid oceanic climate with abundant precipitation over the year, while northeastern and southeastern regions are mainly characterized by semiarid conditions with annual precipitation generally below 300 mm [40].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed the high occurrence of severe droughts episodes in Spain through historical [28][29][30] and instrumental records [31]. Spain has strong climatic contrasts with marked spatial and seasonal differences in precipitation [32][33][34][35] and AED [36][37][38][39]. Northern Spain is characterized by its humid oceanic climate with abundant precipitation over the year, while northeastern and southeastern regions are mainly characterized by semiarid conditions with annual precipitation generally below 300 mm [40].…”
Section: Introductionmentioning
confidence: 99%
“…), and Monte Alto (42 • 33 N, 1 • 06 W, 705 m a.s.l.). Similar climatic conditions characterise the sites [31,32]. Following the Köppen classification, the climate in the study region is classified as Temperate Oceanic (Cfb) [33].…”
Section: Study Sites and Thinningmentioning
confidence: 99%
“…The dataset is based on the entire daily observational information from the National Spanish Meteorological Service (AEMET), which was subjected to a thorough quality control and homogenization process (Tom as-Burguera et al, 2016). Details of the process followed in developing the dataset are available in Tomas-Burguera et al (2019). The reference evapotranspiration (ET o ), a robust metric of the AED (Vicente-Serrano et al, 2020), was calculated from the maximum and minimum temperature, relative humidity, wind speed, and sunshine duration, using the FAO-56 Penman-Monteith equation (Allen et al, 1998).…”
Section: Atmospheric Evaporative Demand Datasetmentioning
confidence: 99%